Prevalence of dyspnea among hospitalized patients at the time of admission - Stevens, Jennifer P. (J Pain Symptom Manage, 2018)
CONTEXT: Dyspnea is an uncomfortable and distressing sensation experienced by hospitalized patients. OBJECTIVES: There is no large-scale study of the prevalence and intensity of patient-reported dyspnea at the time of admission to the hospital. METHODS: Between March 2014 and September 2016, we conducted a prospective cohort study among all consecutive hospitalized patients at a single tertiary care center in Boston, MA. During the first 12 hours of admission to medical-surgical and obstetric units, nurses at our institution routinely collect a patient’s (1) current level of dyspnea on a 0-10 scale with 10 anchored at “unbearable”, (2) worst dyspnea in the past 24 hours prior to arrival at the hospital on the same 0-10 scale, and (3) what activities were associated with dyspnea prior to admission. The prevalence of dyspnea was identified and tests of difference were performed across patient characteristics. RESULTS: We analyzed 67,362 patients, 12% of whom were obstetric patients. Fifty percent of patients were admitted to a medical-surgical unit following treatment in the ED. Among all non-critically ill inpatients, 16% of patients experienced dyspnea in the 24 hours prior to the admission. Twenty-three percent of patients admitted through the emergency department reported any dyspnea in the past 24 hours. Eleven percent experienced some current dyspnea when interviewed within 12 hours of admission with 4% of patients experiencing dyspnea that was rated 4 or greater. Dyspnea of 4 or more was present in 43% of patients admitted with respiratory diagnoses and 25% of patients with cardiovascular diagnoses. After multivariable adjustment for severity of illness and patient comorbidities, patients admitted on the weekend or during the overnight nursing shift were more likely to report dyspnea on admission. CONCLUSIONS: Dyspnea is a common symptom among all hospitalized patients. Routine documentation of dyspnea is feasible in a large tertiary care center.